(untitled) (Bulletin of Armenian Libraries, 2023)
The presentation examines Artashes Ter-Khachaturyan’s studies devoted to Armenian periodicals from the core of his historical- philological research heritage. Over the years, he collected samples of the periodicals published in different colonies of the Armenian diaspora, not only studying and making them valuable publications, but also organizing exhibitions in different parts of the world, promoting and making known this important part of national printing heritage.